CONFRONTING AND DEMYSTIFYING HARMFUL PARTICIPATORY CULTURES - Inwood, Olivia; Ippolito, Heidi; Laminack, Michael (AoIR Selected Papers of Internet Research, 2023)
This year’s AoIR gathering calls us to consider how "new colonizing forces” are “re-fashioning the world in their own image,” and how we might resist such persistent narratives of destructive domination. Our panel examines various modes of online participatory culture and community building through three different frameworks: undetected semiotic affiliation on YouTube, the participatory religious storytelling of QAnon, and the neoliberal self-colonization of MLMs. Our collective aim is to expose existing colonial structures in online spaces (as well as their offline roots) and break them down in order to offer something new. We offer three interdisciplinary approaches that weave together a story about the desire for community and connection. Persistent narratives of individualism compete with the desire for welcoming spaces and shared values, but a long history of colonized internet threatens to reinforce linguistic and narrative hegemony within these online communities. These papers dive deep into the complex problem of finding kinship through destructive worldviews and alternative histories. Unless we find sustainable ways of recognizing and dispelling these pockets of fringe communities, they will inevitably continue to grow and draw in more participants. In a climate of rising individualism and distrust in institutions, communal spaces will continue to be a place of important contestation. People will inevitably gravitate toward (online) communities, but there is a growing concern about what sorts of communities gain the most traction and participants. This panel asks: How can we create more robust safeguards, more compelling stories, and less profit-driven modes of existing in community?